Natural Convection in Superposed Fluid-Porous Layers - Bagchi, Aniruddha; Kulacki, Francis A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Natural Convection in Composite Fluid-Porous Domains provides a timely overview of the current state of understanding on the phenomenon of convection in composite fluid-porous layers. Natural convection in horizontal fluid-porous layers has received renewed attention because of engineering problems such as post-accident cooling of nuclear reactors, contaminant transport in groundwater, and convection in fibrous insulation systems. Because applications of the problem span many scientific domains, the book serves as a valuable resource for a wide audience.
Introduction -- Literature Review -- Mathematical Formulation and Numerical Solution -- Numerical Prediction of Convection -- Measurement of Heat Transfer Coefficients -- Discussion.
Keywords: Engineering; Hydraulic engineering; Nuclear engineering; Engineering; Engineering Fluid Dynamics; Energy Systems; Nuclear Engineering; Hydrogeology